Sulfur dioxide in the Venus atmosphere: I. Vertical distribution and variability - Vandaele, A; Korablev, O; Belyaev, D; Chamberlain, S; Evdokimova, D; Encrenaz, T; Esposito, L; Jessup, K; Lefèvre, F; Limaye, S; Mahieux, A; Marcq, E; et al. (Elsevier, 2017)
Recent observations of sulfur containing species (SO2, SO, OCS, and H2SO4) in Venus’ mesosphere have generated controversy and great interest in the scientific community. These observations revealed unexpected spatial patterns and spatial/temporal variability that have not been satisfactorily explained by models. Sulfur oxide chemistry on Venus is closely linked to the global-scale cloud and haze layers, which are composed primarily of concentrated sulfuric acid. Sulfur oxide observations provide therefore important insight into the on-going chemical evolution of Venus’ atmosphere, atmospheric dynamics, and possible volcanism. This paper is the first of a series of two investigating the SO2 and SO variability in the Venus atmosphere. This first part of the study will focus on the vertical distribution of SO2, considering mostly observations performed by instruments and techniques providing accurate vertical information. This comprises instruments in space (SPICAV/SOIR suite on board Venus Express) and Earth-based instruments (JCMT). The most noticeable feature of the vertical profile of the SO2 abundance in the Venus atmosphere is the presence of an inversion layer located at about 70-75 km, with VMRs increasing above. The observations presented in this compilation indicate that at least one other significant sulfur reservoir (in addition to SO2 and SO) must be present throughout the 70-100 km altitude region to explain the inversion in the SO2 vertical profile. No photochemical model has an explanation for this behaviour. GCM modelling indicates that dynamics may play an important role in generating an inflection point at 75 km altitude but does not provide a definitive explanation of the source of the inflection at all local times or latitudes The current study has been carried out within the frame of the International Space Science Institute (ISSI) International Team entitled ‘SO2 variability in the Venus atmosphere’.